A REPRESENTAÇÃO DO MASCULINO: UM OLHAR SEMIÓTICO SOBRE A PUBLICIDADE NAZISTA - FRANÇA, KÁTIA APARECIDA BIZAN (2019)
The propaganda cultivates the imaginary universe of peculiar desires through manipulation, persuasion and seduction in order to convince. Based on this premise, this work aims to analyze how propaganda made use of posters to articulate their speech in the cultural panorama of the German people during the Second World War. By means of semiotic analysis, it was analyzed the masculine representation in the German government propagandas, that worked with the identity, cultural and ideological reinterpretation in its graphics and in its arguments using the man sign. It is demonstrated here that the Nazi ideology were very well structured, applying strategies for the conquest in order to achieve support and participation of a people who were thirsty for hope and needed models of heroes or gods to guide them. In this line of strategy, humanized models of gods / heroes were publicized as inspiration for men to become warriors in defense of Germany, as well to help the government financially, armamentarily in the manufacture of weapons and to collaborate in the persecutions of people who did not fit into the requirement.